2021
DOI: 10.3904/kjim.2021.026
|View full text |Cite
|
Sign up to set email alerts
|

Changes in respiratory virus infection trends during the COVID-19 pandemic in South Korea: the effectiveness of public health measures

Abstract: Background/Aims: Studies on the effectiveness of public health measures to prevent respiratory virus transmission in real-world settings are lacking. We investigated the effectiveness of universal mask use and adherence to other personal preventive measures on the changing viral respiratory infection patterns during the coronavirus disease 2019 (COVID-19) pandemic.Methods: Data were extracted from the South Korean National Respiratory Virus Sentinel Surveillance System. During the COVID-19 pandemic, a cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…Most studies analyzed the epidemiology of respiratory viral infections during the pandemic compared to the 5 years prior to the COVID-19 pandemic. Four studies [ 8 , 10 , 13 , 14 ] analyzed all 8 viruses (adenovirus [ADV], parainfluenza virus, respiratory syncytial virus, influenza virus [IFV], human coronavirus, human rhinovirus [HRV], human bocavirus [HBoV], and human metapneumovirus) reported in the surveillance system data, while the other 6 studies [ 6 , 7 , 9 , 11 , 12 , 15 ] analyzed some of the viruses. Of those 6 studies, 4 were of IFV [ 6 , 9 , 11 , 12 ].…”
Section: Changes In Respiratory Disease Epidemiologymentioning
confidence: 99%
“…Most studies analyzed the epidemiology of respiratory viral infections during the pandemic compared to the 5 years prior to the COVID-19 pandemic. Four studies [ 8 , 10 , 13 , 14 ] analyzed all 8 viruses (adenovirus [ADV], parainfluenza virus, respiratory syncytial virus, influenza virus [IFV], human coronavirus, human rhinovirus [HRV], human bocavirus [HBoV], and human metapneumovirus) reported in the surveillance system data, while the other 6 studies [ 6 , 7 , 9 , 11 , 12 , 15 ] analyzed some of the viruses. Of those 6 studies, 4 were of IFV [ 6 , 9 , 11 , 12 ].…”
Section: Changes In Respiratory Disease Epidemiologymentioning
confidence: 99%
“…Few recent studies have shown a decrease in multiple respiratory agents. [22][23][24][25][26] Interestingly, a case series study, that investigated hospitalisation rates of children under the age of 2 years due to lower respiratory infections, revealed a significant reduction in hospitalisation mainly caused by enveloped viruses. Incidence of unenveloped viruses such as rhinoviruses/enteroviruses did not show such impressive decrease.…”
Section: Discussionmentioning
confidence: 99%
“…The lower basic reproduction number (R 0 ) of influenza20 and IMD21 compared with that of SARS-CoV-2, is a possible explanation for the much stronger impact that those measures had on their transmission. Few recent studies have shown a decrease in multiple respiratory agents 22–26. Interestingly, a case series study, that investigated hospitalisation rates of children under the age of 2 years due to lower respiratory infections, revealed a significant reduction in hospitalisation mainly caused by enveloped viruses.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of Park et al, surveillance data from the South Korean National Respiratory Virus Sentinel Surveillance System showed a decreased number of hospitalized patients with acute viral respiratory infections in 2020. The peak of influenza-like illness during the COVID-19 epidemic was significantly lower than in 2016–2019 (48.8 cases per 1000 patients versus 86.2 cases per 1000 patients [ 14 ]. At Chongqing Health Center for Women and Children, China [ 15 ], before the COVID-19 pandemic, the pediatric outpatient volume showed an increasing trend from 2017 to 2019.…”
Section: Discussionmentioning
confidence: 99%